(3EOGQI GdeDSSGJ GdUMajI (B:s (3OQGSI aj GdhGbY h GdeSJMOKGJ (B/s - (3QHjY, YHO GdLhGO SYjO eMeOs ((3GdbGgQI (B:s (3OGQ GdaLQ ddfTQ h GdJhRjY ,s, 2004)
(3JfGhd eaghe GdfXe GdEOGQjI h YdGbJgG HGdeDSSGJ GdUMajI aj YUQ JcfhdhLjG GdeYdheGJ MjK bSeJ aUhd GdcJGH Gdi(B10(3aUhd cd aUd eSJbd HPGJgs
Keywords: (3EOGQI GdeDSSGJs; (3GdUMGaIs; (3JcfhdhLjG GdeYdheGJs